- #1

- 409

- 1

## Homework Statement

Show that [tex] \psi (\gamma^a\phi)=-(\gamma^a\phi)\psi [/tex]

## Homework Equations

Maybe [tex] \{\gamma^a, \gamma^b\}=\gamma^a\gamma^b+\gamma^b\gamma^a=2\eta^{ab}I [/tex]

Perhaps also:

[tex] (\gamma^0)^{\dag}=\gamma^0 [/tex] and [tex] (\gamma^i)^{\dag}=-(\gamma^i) [/tex]

## The Attempt at a Solution

The gammas are matrices so I guess we start with

[tex] \psi_{\mu}[(\gamma^a)^{\mu\nu}\phi_{\nu}] [/tex]

[tex] =\psi_{\mu}[(((\gamma^a)^*)^{\dag})^{\nu\mu}\phi_{\nu}] [/tex]

[tex] =-[(((\gamma^a)^*))^{\nu\mu}\psi_{\mu}]\phi_{\nu} [/tex]

Which looks almost correct except the *, and also I'm not sure if I was supposed to assume that a can only refer to spatial indices, not the 0 which is equal to its hermitian conj, not minus it.

Thanks for any help